The Lived Experiences of the Special Program in the Arts Learners in their Online Performance Tasks - Rotsen V. Escorial; Irish S. Escorial (PT ARRUS Intelektual Indonesia, 2024)
With the pandemic caused by COVID-19, many people worldwide have been compelled to the new ways of education. This study explored the experiences of Special Program in the Arts learners in their online performance tasks in the different specializations in new normal education. The study was conducted in Kapatagan National High School, Division of Lanao del Norte. The study utilized the qualitative approach using the phenomenological research design. The study included twenty-one participants identified through purposive sampling. An Interview Guide question was used for in-depth interviews. The researcher employed the seven steps of Colaizzi's method of data analysis Results revealed the following themes: Lacking of Learning Resources in Online Performance Tasks; Adjusting to Shifting of the Learning Process; Deficiency in Understanding Concepts; and Difficulty in Doing Online Performance Activities. Results showed that SPA learners experienced a lot of challenges and difficulties in their online performance tasks. In their online skills demonstration, learners were unable to comprehend and follow specific instructions. Learners prefer classroom learning over virtual because it is convenient and they can learn better. Teachers could resort to social media or any other online platforms to connect with the students and assist them in their lessons as they were doing self-learning at home. Teachers may provide digital instructional materials such as videos or link to give learners with a coherent learning experience.